2017
DOI: 10.1001/jamasurg.2016.3644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyglycolic Acid Mesh for Prevention of Pancreatic Fistula Following Distal Pancreatectomy

Abstract: clinicaltrials.gov Identifier: NCT01550406.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 26 publications
2
78
0
1
Order By: Relevance
“…The original search strategy identified 1205 potentially relevant articles, yielding 16 RCTs that satisfied the inclusion and exclusion criteria, and were therefore included in the quantitative analysis ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original search strategy identified 1205 potentially relevant articles, yielding 16 RCTs that satisfied the inclusion and exclusion criteria, and were therefore included in the quantitative analysis ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed consistently well in the complete reporting of data, limiting the risk of attrition bias, and random sequence generators used were generally efficacious. However, notable deficiencies were identified in blinding of the outcome assessment (12 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycolic acid mesh is a bioabsorbable recombinant membrane made of a synthetic polymer with a cellulose‐like structure . A randomized control trial testing the ability of PGA mesh to reduce POPF after distal pancreatectomy reported that the rate of clinically relevant POPF (Grade B or C) was significantly lower in the PGA group than in the control group (11.4% vs. 28.3%, P = 0.040) . Following the completion of pancreaticojejunostomy, surgeons can easily wrap the anastomotic site with PGA mesh because it is easy to manipulate.…”
Section: Discussionmentioning
confidence: 99%
“…The PGA mesh was used in many surgical procedures, for the prevention of CSF leakage during dura repair of spine and for hemostasis of splenic rupture [29,30]. This finding was in good agreement with other studies showing the efficacy of PGA mesh after pancreatic resection [13,14,28].…”
Section: Discussionmentioning
confidence: 99%